Monitoring and controlling real-time bus services: a reinforcement learning procedure for eliminating bus bunching - Comi, Antonio; Sassano, Mario; Valentini, Alessio (Transportation research procedia (Online), 2022)
Bus bunching is one of the main issues encountered in bus service operations. The headway (i.e., time between two successive buses) of high-frequency services operating on congested routes can be subject to significant variability with two or more buses arriving at the same bus stop and at the same time (bus bunching). This affects the reliability of bus services and causes user frustration with the travel experience. Although public transport is encouraged as the most environment-friendly mass transit solution, bus bunching is undesirable given that it creates inefficiencies and can push passengers to use private transport. The advances in information communication technologies (ICTs) offer new opportunities for transit operators to limit this effect, ensuring a more reliable service. The paper, taking advantage of the innovations in ICTs, proposes a machine learning-based procedure addressing the issues causing bus bunching. The procedure is applied to a real test case with encouraging results. It opens the possibility that it may be incorporated in a decision support system to assist operators (drivers) in taking corrective actions throughout the day, improving bus service operations.